The stages of transformation of the society’s reflection in kazakh feature films (Herald of Journalism, 2016)
In this paper discusses the issues of transformation of traditional so ciety’s reflection in the Kazakh feature film – Kazakh village in modern society. Modern Kazakh city carries echoes of powerful social upheavals, which was subject to a traditional society as a result of the October revo lution of 1917, the formation of the soviet state, forced collectivization, famine, physical destruction of the national intelligentsia during the Stalin ist repression called «red terror», colonial cultural policy with the change in the two decades of the alphabet with the Arabic alphabet to the Latin alphabet first, then to the Cyrillic alphabet, virgin lands campaign, when there were plowed pasture land of Kazakhs.
Keywords: cinematograph, feature film, traditional and modern soci ety, village, city, censorship, ideology.